Pengaruh Brand Image, Brand Ambassador, dan Product Quality Terhadap Keputusan pembelian Sepatu Adidas (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2020) - Saputra, Rizki Julianto; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to examine the influence of Brand Image, Brand Ambassador, and Product Quality on the purchasing decision of Adidas shoes among students of the Faculty of Economics and Business at Universitas Islam Malang, class of 2020. This research uses explanatory research methods with a quantitative approach, testing the relationships between variables by testing the proposed hypotheses. The sample consists of 90 participants who are Adidas shoe buyers at Universitas Islam Malang, selected using snowball sampling and purposive sampling techniques. Data were collected through questionnaires using a Likert scale. The analysis results show that Brand Image, Brand Ambassador, and Product Quality simultaneously have a significant effect on purchasing decisions of Adidas shoes. Specifically, Brand Image does not have a significant effect, while Brand Ambassador and Product Quality have a positive and significant impact on purchasing decisions. Keywords: Brand Image, Brand Ambassador, Product Quality, Purchasing Decision.